PELATIHAN PENGOLAHAN MINYAK JELANTAH PADA BUMDES PULOTONDO, KEC. NGUNUT – KAB. TULUNGAGUNG - Soedarso, Elvyra Handayani; Berlianingtyas, Putri Ayu; Kristanti, Ima; Rachmat, Basuki; Ernawati, Widi Dwi; Yusna, Yusna (Jurnal Abdimas Sangkabira, 2024)
The village of Pulotondo, in the Ngunut subdistrict of Tulungagung Regency, has significant potential for freshwater fish farming and horticultural plant cultivation. However, this potential remains underutilized because the marketing area is still limited to the local scope. The local BUMDes (Village-Owned Enterprises) has not seized this opportunity and is only focusing on a micro-scale LPG retail business for the surrounding community. The event can provide BUMDes Pulotondo for utilizing waste processing, specifically converting used cooking oil into scented candles. This could reduce used cooking oil waste and allow the candles to be sold, thereby boosting BUMDes's economic potential. The service method includes material presentation, discussions, and practical exercises. Making candles from used cooking oil proceeded smoothly and was well-received by 12 participants, and they can produce candles for product sale.